Strategic Portfolio Building in Donors' Multilateral Institutional Choice - Baran Han (East Asian Economic Review (EAER), 2021)
More donors are formally assessing their multilateral aid disbursement policies as well as the multilateral institutions that they contribute to. Analyzing OECD Creditor Reporting System data from 2011 to 2019 of 23 donors and 34 multilateral organizations, we find evidence of institutional portfolio building of donors to align multilateral and bilateral aid channels. Such tendency is more pronounced for core-funding than multi-bi funding and much stronger at the recipient country level than at the sectoral level. Smaller donors that operate from a limited multilateral budget show greater preferences for geographical similarity. When donors give to institutions with sectoral specialization, they seek sectoral similarity with their bilateral aid.
Keywords: F35; F53; O10; 330; Multilateral Aid; Multi-bi Aid; Sector Complementarity; Geographical Complementarity; Multilateral Institution Portfolio